A Healthier Antioxidants-Rich Food with Vitamin C and E - Linda Chiuman; Nelvi Sutanto (GLOBAL HEALTH SCIENCE GROUP, 2020)
There is no doubt that the incredible advances in medicine will be perceived as one of the spectacular achievements of the twentieth century right along with some other innovations. Hazards such as radiation, pollution, smoke, nutrient poor diet handle many common diseases. This article demonstrates knowledge of the antioxidant to practice real preventive medicine by understanding the role that free radicals play in the onset and progression of known disease and how antioxidants can control them. Keywords: antioxidant; antioxidant activity; free radicals, vitamin C, vitamin E